Heat stress and plant development: role of sulphur metabolites and management strategies. (19th May 2019) - Ihsan, Muhammad Zahid; Daur, Ihsanullah; Alghabari, Fahad; Alzamanan, Saleh; Rizwan, Shahid; Ahmad, Maqshoof; Waqas, Muhammad; Shafqat, Waqas
ABSTRACT: Temperature plays a crucial role in plants development whereas a sudden rise may cause severe consequences. Heat stress impairs plant growth, photosynthesis, pollen development and reproduction. The plant photosynthetic efficiency is mainly reduced by the over production of reactive oxygen species, denaturation of heat shock proteins and alteration in many enzymes activities. Unlike drought stress, plants have developed a very few mechanisms to encounter heat stress problem. Recently, the use of nutrients such as sulphur has emerged as one of the efficient methods to enhance plant tolerance against high temperature stress. The mechanistic understanding of sulphur-based strategies could be very helpful to sustain plant development and global food supplies in future hotter climates. The present review mainly focuses on (1) high temperature induced changes in plant functions, (2) possible roles of sulphur metabolites in heat stress tolerance and (3) possibilities of using sulphur as a management strategy. Moreover, the review consolidates the future research needs that must focus on (i) heat tolerant germplasm screening; (ii) sulphur dose optimisation, application method and crop growth stages response; (iii) finding of sulphur induced heat tolerance mechanisms and (iv) the use of omic approaches to discover sulphur metabolites role in heat stress tolerance.